The CONSTANS-LIKE SlCOL1 in tomato regulates the fruit chlorophyll content by stabilizing the GOLDEN2-LIKE protein - Long Cui; Fangyan Zheng; Chenhui Zhang; Sunan Gao; Jie Ye; Yuyang Zhang; Taotao Wang; Zonglie Hong; Zhibiao Ye; Junhong Zhang (Journal of Integrative Agriculture, 2025)
CONSTANS (CO) and CONSTANS-LIKE (COL) transcription factors are known to regulate a series of cellular processes, including the transition from vegetative growth to flower development in plants. However, their role in regulating the fruit chlorophyll content is poorly understood. In this study, SlCOL1, the tomato (Solanum lycopersicum) ortholog of Arabidopsis CONSTANS, was shown to play key roles in controlling fruit chlorophyll. The suppression of SlCOL1 expression led to a reduction in the chlorophyll content of immature green fruit, while the overexpression of SlCOL1 increased it. An analysis of protein–protein interactions indicated that SlCOL1 forms a complex with GOLDEN2-LIKE (GLK2), which promotes the stability of its protein. The overexpression of SlCOL1 in the glk2 null mutation background of tomato failed to promote chlorophyll accumulation in the immature green fruit, which suggests that GLK2 is required for the function of SlCOL1 in regulating chlorophyll content. These results shed new light on the mechanisms used by COL1 and GLK2 to regulate fruit development and chlorophyll accumulation in tomato.